Firm size and monetary policy transmission: evidence from German business survey data - Michael Ehrmann (European Central Bank (ECB), 2000)
Using business survey data on German manufacturing firms, this paper provides tests for hypotheses formulated in capital market imperfection theories that predict distributional effects in the transmission mechanism of monetary policy. Effects of monetary policy shocks on the business conditions of firms of several size classes are analysed, with the finding of considerable asymmetry. As predicted by theory, small firms are affected more strongly than large firms. To test whether these effects are reinforced when the economy is in a business cycle downturn, the paper employs a new estimation strategy: impulse response analysis conditional on Markov-switching regimes. The findings are supportive of the theoretical hypotheses: in a business cycle downturn, the distributional effects of monetary policy transmission are indeed reinforced.
Keywords: E52; E44; C32; 330; balance sheet channel; firm size; Markov switching; Monetary policy transmission